Epilepsi Terkait Tumor Otak sebagai Presentasi Awal Metastasis Intrakranial - Riky Candra; Arya Marganda Simanjuntak; Yossi Maryanti (Jurnal Ilmu Kedokteran, 2026)
Brain tumor-related epilepsy (BTRE) occurs in approximately 35–70% of patients with brain tumors, and in 20–40% of cases, seizures represent the initial manifestation before tumor diagnosis. New-onset seizures in adults without prior epilepsy should raise suspicion for an underlying structural intracranial lesion, including brain metastasis. A 55-year-old man presented with three seizure episodes within one month. The seizures began with unilateral tonic stiffness that progressed to bilateral tonic–clonic seizures with impaired awareness, followed by postictal confusion. The patient also reported progressive headache, left-sided weakness, and cognitive decline. Neurological examination revealed left hemiparesis and impaired cognitive function. Contrast-enhanced brain CT demonstrated multiple intracranial lesions with surrounding edema and midline shift, consistent with brain metastases. Thoracic imaging revealed a left lung mass suggestive of a primary malignancy. This case highlights that new-onset seizures in adulthood, particularly when accompanied by progressive neurological deficits, should prompt evaluation for intracranial metastasis. Early recognition of BTRE as an initial presentation of brain tumors is essential for timely diagnosis and appropriate management.